Antagonistic effects and mechanisms of carbendazim and chlorpyrifos on the neurobehavior of larval zebrafish. (April 2022) - Zhang, Wanjun; Fan, Ruiqi; Luo, Sunlin; Ying liu,; Jin, Yongpeng; Li, Yongchen; Xiong, Mengqin; Yuan, Xiaoyan; Jia, Li; Chen, Yiqiang
Abstract: Residues from multiple pesticides are frequently detected on vegetables, which may produce combined toxicity not predicted by individual toxicity data. As these combined effects present additional dangers to food safety, we have compared individual to combined effects for a variety of pesticides. Carbendazim and chlorpyrifos are the two most commonly detected pesticides in vegetables, and previous studies reported that combined exposure results in synergistic developmental toxicity to zebrafish embryos. In this study, individual and combined effects on zebrafish motor activity were examined following individual and combined exposure to assess nervous system toxicity. Further, transcriptomics methods were used to identify potential molecular mechanisms for individual and combined toxicity. Carbendazim alone induced a disorganized swim pattern characterized by increased angular velocity, turn angle, meander, and acceleration during light-dark transition, while chlorpyrifos alone reduced average swim speed and light-dark acceleration. Combined treatment significantly reduced average swim velocity and total distance traveled. Combination indices indicated strong antagonism between compounds for average speed and light-dark acceleration. Transcriptomics (RNA-seq) showed that carbendazim significantly altered the expression of genes involved in antigen processing and presentation, apoptosis, autophagy, and metabolism, including ctslb, cyp7a1, hsp70l, and ugt1a1 . Alternatively, chlorpyrifos significantly altered genes involved in various nervous system-related pathways, including glutamatergic, GABAergic, dopaminergic, and calcium signaling. Protein-protein interaction (PPI) network analysis suggested that chlorpyrifos significantly downregulated genes related to light transduction, resulting in decreased sensitivity to light-dark transitions, while antagonism mainly reflected divergent effects on phototransduction and retinol metabolism. Carbendazim had no significant effects on vision-related genes such as gnat1 and gngt1, while chlorpyrifos downregulated expression, an effect reversed by the combination. Comprehensive toxicity analyses must include joint effects of co-applied pesticides for enhanced food safety. Graphical abstract: Image 1 Highlights: Carbendazim promoted while chlorpyrifos depressed motor activity in zebrafish. When combined, carbendazim antagonized the effects of chlorpyrifos. Antagonism may stem from reciprocal regulation of light transduction. Changes in gnat1, gngt1, elovl4b, and grk7a expression are markers for antagonism.